Role of economists in policy-making - Montek S. Ahluwalia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper reviews the many areas in which economists play an important role in policy-making, including the quantification of objectives set by political processes, formulation of macroeconomic policy where economists have a dominating role, and also the formulation of sectoral policy where they work in combination with sector experts. It emphasizes that economics is not a sufficiently precise science to ensure that there is wide agreement among economists on all aspects of economic analysis but an articulation of these differences helps policy makers and the public to make more informed decisions. It also highlights the importance of independent review of the effectiveness of policy programmes as an essential support for policy-making.
Keywords: 330; multi-dimensional objectives; macro policy; sectoral policy